2012
DOI: 10.1093/geronb/gbs055
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Concern and Perspective Taking: Linear and Quadratic Effects of Age Across the Adult Life Span

Abstract: We discuss the inverse-U-shaped age pattern, in terms of aging versus cohort influences, and how it complements and extends the existing literature on empathy and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
209
6
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(255 citation statements)
references
References 33 publications
31
209
6
9
Order By: Relevance
“…Unlike in prior research (O'Brien, Konrath, Grühn, & Hagen, 2013), gender was unrelated to perspective taking, β=.00, p=.96. However, perspective taking was significantly associated with higher social desirability, β=.26, p<.001, as has been found in prior research (Watson & Morris, 1991).…”
Section: Descriptive Statistics Seecontrasting
confidence: 95%
See 1 more Smart Citation
“…Unlike in prior research (O'Brien, Konrath, Grühn, & Hagen, 2013), gender was unrelated to perspective taking, β=.00, p=.96. However, perspective taking was significantly associated with higher social desirability, β=.26, p<.001, as has been found in prior research (Watson & Morris, 1991).…”
Section: Descriptive Statistics Seecontrasting
confidence: 95%
“…Gender was significantly associated with empathic concern, β=-.12, p<.001, with males scoring lower than females as per prior research (O'Brien et al, 2013). In addition, empathic concern was positively associated with social desirability, β=.13, p<.001, also replicating prior research (Watson & Morris, 1991).…”
Section: Descriptive Statistics Seesupporting
confidence: 76%
“…Despite the extensive history of behavioral psychology and philosophy research, the definition of empathy differs from study to study and has no universally accepted definition (Batson, 2009;Eisenberg, 2000). A large number of studies on empathy stress that the construct is multifaceted, but it is composed of at least two important components (Decety & Jackson, 2004;Decety & Ickes, 2009;Decety, Michalska, & Kinzler, 2012;Eres, Decety, Louis, & Molenberghs, 2015;O'Brien, Konrath, Gruhn, & Hagen, 2013): an affective component, which is defined as the ability to experience an appropriate emotional response of another's state (O'Brien et al, 2013), and a cognitive component, which is related to our capacity to predict and understand another's mental state using cognitive processes (Decety et al, 2012). When we empathize, we vicariously experience the emotional state of the other person while realizing that what we are feeling is not our own affective state but that of another person.…”
mentioning
confidence: 99%
“…New technology as both a cause and solution for declining empathy Over the past several decades, there have been documented declines in face-to-face social interactions, and in young people's self-perceived ability to care and connect with others (Konrath, Chopik, Hsing, & O'Brien, 2014;Konrath, et al, 2011;O'Brien, Konrath, Grühn, & Hagen, 2013;Putnam, 2000;Twenge, Konrath, Foster, Campbell, & Bushman, 2008). For example, our research has found that the personality trait narcissism has risen since the early 1980s among American college students , while dispositional empathic concern and perspective taking have simultaneously been declining (Konrath, et al, 2011).…”
Section: The Malleability Of Empathymentioning
confidence: 99%
“…Three commonly used components of empathic character arose from this process: 1) Emotional empathy, also known as empathic concern or compassion (Davis, 1983c;Galinsky, Maddux, Gilin, & White, 2008;O'Brien, et al, 2013), 2) Cognitive empathy, also known as perspective taking or role taking (Batson, Early, & Salvarani, 1997;Davis, 1983c;Galinsky, et al, 2008) (O'Brien, et al, 2013, and 3) Prosocial behavior as a potential consequence of empathy, such as helping or sharing (Eisenberg & Miller, 1987;Eisenberg et al, 1989). Control group messages were designed to capture both the emotional and the cognitive aspects of low empathy.…”
Section: Study Design and Measures Developing The Text Messagesmentioning
confidence: 99%